The validity of the session-RPE method for quantifying training load in water polo - Lupo, C.; Capranica, L.; Tessitore, A. (International Journal of Sports Physiology and Performance, 2014)
Context: The assessment of internal training load (ITL) using the session rating of perceived exertion (session RPE) has been demonstrated to provide valuable information, also in team sports. Nevertheless, no studies have investigated the use of this method during youth water polo training. Purpose: To evaluate youth water polo training, showing the corresponding level of reliability of the session-RPE method. Methods: Thirteen male youth water polo players (age 15.6 ± 0.5 y, height 1.80 ± 0.06 m, body mass 72.7 ± 7.8 kg) were monitored during 8 training sessions (80 individual training sessions) over 10 d. The Edwards summated heart-rate-zone method was used as a reference measure of ITL; the session-RPE rating was obtained using CR-10 scale modified by Foster. The Pearson product-moment was applied to regress the Edwards heart-rate-zone method against CR-10 session RPE for each training session and individual data. Results: Analyses reported overall high (r = .88, R2 = .78) and significant (P < .001) correlations between the Edwards heart-rate and session-RPE methods. Significant correlations were also shown for each training session (r range .69-.92, R2 range .48-.85, P < .05) and individual data (r range .76-.98, R2 range .58-.97, P < .05). Discussion: The results confirmed that the session-RPE method as an easy and reliable tool to evaluate ITL in youth water polo, allowing coaches to efficiently monitor their training plans.